Graft quality matters: Survival after simultaneous liver‐kidney transplant according to KDPI. Issue 5 (28th March 2017) - Jay, Colleen; Pugh, Jacqueline; Halff, Glenn; Abrahamian, Greg; Cigarroa, Francisco; Washburn, Ken
Abstract: Background: Poor renal function is associated with higher mortality after liver transplantation. Our aim was to understand the impact of kidney graft quality according to the kidney donor profile index (KDPI) score on survival after simultaneous liver‐kidney (SLK) transplantation. Methods: Using United Network of Organ Sharing data from 2002 to 2013 for adult deceased donor SLK recipients, we compared survival and renal graft outcomes according to KDPI. Results: Of 4207 SLK transplants, 6% were from KDPI >85% donors. KDPI >85% recipients had significantly increased mortality (HR=1.83, 95%CI=1.44‐2.31) after adjusting for recipient factors. Additionally, dialysis in the first week (HR=1.4, 95%CI=1.2‐1.7) and death‐censored kidney graft failure at 1 year (HR=5.7, 95%CI=4.6‐7.0) were associated with increased mortality after adjusting for recipient factors and liver donor risk index score. Conclusions: KDPI >85% recipients had worse patient and graft survival after SLK. Poor renal allograft outcomes including dialysis in the first week and death‐censored kidney graft failure at 1 year, which occurred more frequently with KDPI >85% grafts, were associated with significantly reduced patient survival. Questions remain about the survival impact of liver vs kidney graft quality given the close relationship between donor factors contributing to both, but KDPI can still be valuable as a metric readily available at the time of organ offers for SLK candidates.